1978_11 The Daily Collegian November 1978 - Associated Students of Fresno State::::::::: (Associated Students of Fresno State, Fresno, Calif.)
Daily (except weekends) during the school year. Microfilm. Palo Alto, Calif. : BMI Library Microfilms, 1986- microfilm reels ; 35 mm. Vol.1, no.1 (Feb 8, 1922)-